The Impact of Malocclusion Severity on Self-Confidence and Facial Appearance among Orthodontic Patients: Malocclusion Severity and Self-Confidence - Zakai, Alima Mohsin; Khatri, Muhammad Siddique; Qurban, Esha; Jabbar, Abdul; Shah, Sana; Memon, Anny (Pakistan Journal of Health Sciences, 2024)
Malocclusion was a group of dental deviations that have a particular psychological influence on the society. Objective: To assess the correlations between malocclusion severity and its effects on self-confidence and facial appearance in patients seeking orthodontic treatment. Methods: The hospital-based study was performed at Orthodontic Department, Institute of Dentistry of Liaquat University of Medical and Health Sciences, Jamshoro. Participants aged 7 to 30 years who were diagnosed with varying degrees of malocclusion, were included in the study while those with congenital or traumatic facial deformities unrelated to malocclusion were excluded from the study. Data were collected via questionnaires (Rosenberg Self Esteem and Dental Aesthetic Index) and clinical assessments. Correlation analysis was used as data analysis. Results: The research comprised of 383 individuals, with 110 (28.7%) were males, and 273(71.3%) females. 361 (94.3%) participants having aesthetics problem, 19 (5.0%) reported with Functional issues, and 3(0.8%) had found with Temporomandibular Joint (TMJ) complications. There were moderate to strong negative correlations between malocclusion severity and self-confidence (r=-0.45, p < 0.05) and between the impact on facial appearance and self-confidence (r=-0.52, p < 0.05) A positive correlation was observed between malocclusion severity and facial appearance impact (r=0.65, p < 0.05) (Table 5). Conclusions: The study found that malocclusion significantly impacts self-confidence and facial appearance, with 71% of participants reporting negative effects on appearance and 47.3% experiencing reduced self-confidence.